Study of prevalence of minimum acceptable diet and associated factors among children aged 6-24 months in rural Gurugram, Haryana, India - Vashist, Sunita; Gupta, Nidhi; Singh, Narendra; Bhawna; Chamola, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: Infant and young child feeding (IYCF) is the key area to improve survival of child and promotion of growth and development of the child. For assessing the IYCF for children aged 6-24 months, minimum acceptable diet (MAD) is one of the core indicators. A community based cross sectional study was done to assess the MAD and its associated factors among children aged 6-24 months in rural Gurugram, Haryana. Methods: A sample of 200 mother-child dyads were interviewed. Majority of children (90.1%) did not receive MAD. Results: The proportion of children who has received minimum diet diversity (MDD) and minimum meal frequency (MMF) were 14% and 61% respectively. More than three fourth (77.5%) of children consumed junk food in last 24 hours dietary recall. Conclusions: Counselling of mothers, encouraging involvement of fathers and extended family members in adequate feeding practices was done.